PENGARUH PENGGUNAAN MULTIMEDIA PRESENTASI BERBASIS ANIMAKER TERHADAP MINAT BELAJAR SENI BUDAYA SISWA SMP - Maulidiyah Azizah Rahmah; Nasir Nasir; Kasman Kasman (Jurnal Riset dan Inovasi Pembelajaran, 2023)
The purpose of this study was to determine the effect of using animaker-based multimedia presentations on students' learning interest. The sample in this study was class VIII.1 with 40 students. The research instrument used observation and a questionnaire. Methods of data collection using observation sheets, questionnaires and documentation. The data analysis technique used is descriptive statistical analysis techniques and inferential statistics. Based on the results of research and data analysis, there is a positive influence on the learning interest of class VIII.1 students of MTs Negeri 1 Makassar City. It can be seen from the descriptive statistical analysis which shows that the percentage of learning media is in the very high category of 94.5% and the percentage of learning interest is in very high category of 87.5%. Based on the results of the hypothesis on the t-test value of 0.05 indicates that the value of α is 0.05 in this study the significant value is 0.000 <0.05 so that H0 is rejected and H1 is accepted. Based on these results, it was concluded that there was a significant influence on the use of Animaker-based presentation media on students' learning interest, so that Animaker media was well used in arts and culture subjects.